The Transcription Regulator Patz1 Is Essential for Neural Stem Cell Maintenance and Proliferation - Mancinelli, Sara; Vitiello, Michela; Donnini, Maria; Mantile, Francesca; Palma, Giuseppe; Luciano, Antonio; Arra, Claudio; Cerchia, Laura; Liguori, Giovanna Lucia; Fedele, Monica (Frontiers in Cell and Developmental Biology, 2021)
Proper regulation of neurogenesis, the process by which new neurons are generated from neural stem and progenitor cells (NS/PCs), is essential for embryonic brain development and adult brain function. The transcription regulator Patz1 is ubiquitously expressed in early mouse embryos and has a key role in embryonic stem cell maintenance. At later stages, the detection of Patz1 expression mainly in the developing brain suggests a specific involvement of Patz1 in neurogenesis. To address this point, we first got insights in Patz1 expression profile in different brain territories at both embryonic and postnatal stages, evidencing a general decreasing trend with respect to time. Then, we performed in vivo and ex vivo analysis of Patz1-knockout mice, focusing on the ventricular and subventricular zone, where we confirmed Patz1 enrichment through the analysis of public RNA-seq datasets. Both embryos and adults showed a significant reduction in the number of Patz1-null NS/PCs, as well as of their self-renewal capability, compared to controls. Consistently, molecular analysis revealed the downregulation of stemness markers in NS/PCs derived from Patz1-null mice. Overall, these data demonstrate the requirement of Patz1 for NS/PC maintenance and proliferation, suggesting new roles for this key transcription factor specifically in brain development and plasticity, with possible implications for neurodegenerative disorders and glial brain tumors.